The Impact of Model, Price, and Quality Factors: Variable Level of Consumer Satisfaction as a Measure in Buying Woven Sarong Products - Devita, Lusy Deasyana Rahma (Universitas Alma Ata, 2023)
The purpose of this study was to investigate the consumer behavior will determine the achievement of company objectives. Consumers will consider a variety of factors related to production. The study was conducted on. The population under study is consumers who've come to buy Gloves loom. The sample used 80 respondents. The variables used in the study include the Model, Price, and Quality Sampling method using purposive sampling with descriptive and statistical analysis techniques including multiple regression analysis. Hypothesis testing with simultaneous test or F-test hypothesis testing with a partial test or t-test and analysis of multiple determination coefficient. The test results simultaneously show variable models, prices, and quality jointly significant effect on customer satisfaction at with Fhitung 186.747. using partial test showed variable model (X1) of 0.3220, the price (X2) is -151, and the quality (X3) of 0.6540 does not have a significant influence on consumer satisfaction. And variable quality (X3) was the dominant effect on customer satisfaction in buying products sarong.